Incidencia económica social en los habitantes y comerciantes beneficiarios con la creación del nuevo mercado 22 de agosto del cantón El Empalme año 2014 - Alvarado Cedeño, Alinson Leonel (2015)
This research was conducted to determine the what was the social economic impact on residents and business beneficiaries with the creation of new market August 22, 2014. El Empalme Canton due to the Canton trade shows disorder, which makes important to develop the next study to serve as a support tool for business planning. In the research two types of survey, the first inhabitants of the village of El Empalme and second were made to traders who are seated in the market August 22, which helped determine what the economic and social benefits has had the market by the survey to residents and traders corner the spliced 2013 it was determined that the inhabitants 68% have a monthly income of $ 500.00 700.00 89% of the inhabitants of the village of El Empalme expressed the new market August 22 would bring to micro-enterprise development thereby creating new jobs. It will also allow the development of new economic activities expressed 83% of the people surveyed Social aspects have been influenced because 73% of traders said that the new market August 22 influenced the social characteristics of the inhabitants purchase. In addition 94% of traders said that improved trading conditions thereby allowing the population to acquire in one place what they want at a lower price.